Evaluation of Antidiabetic Activity of Croton zambesicus Root Extract: In Vivo Inhibitory Effect on Alpha Amylase and Alpha Glucosidase of Rats - Okokon, Jude Efiom; Edem, Utibe Anietie; OSIGWE, Chinyelu Clementina; Uwaeme, Ugonma Florence (Biology, Medicine, & Natural Product Chemistry, 2025)
Diabetes mellitus is a global health challenge, necessitating the need for alternative treatments. Croton zambesicus Muell Arg. (Euphorbiaceace) a medicinal plant used traditionally in the treatment of some ailments was investigated for its inhibitory potential on alpha-amylase and alpha-glucosidase enzymes in rats. The root extract of C. zambesicus (27 - 81 mg/kg) was investigated in vivo for the inhibitory effect on alpha amylase and alpha glucosidase enzymes using starch, sucrose, and maltose as substrates. Acarbose was used as a reference drug. Blood glucose levels (BGL) of rats, post administration of the substrate and extract concurrently, were monitored over 3 hours as a parameter to measure the inhibitory potential of the extract. The root extract dose-dependently caused significant (p<0.05) reduction in blood glucose levels of treated rats with the various substrates used. The results suggest that the root extract of Croton zambesicus has the potentials to inhibit alpha amylase and alpha glucosidase in rats.